CALLUS INDUCTION IN LEAF EXPLANTS OF Cissus verticillata (L.) NICOLSON & C. E. JARVIS - Alves dos Santos, Maurício Reginaldo; Félix da Rocha, Josilene; Santana Paz, Eloísa; Smozinski, Caroline Vivian; de Oliveira Nogueira, Wanessa; de Castro Melo Guimarães, Milene (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2016)
Cissus verticillata (L.) Nicolson & C. E. Jarvis is a perennial plant native to the Amazonian Rainforest. This species is used in Brazilian folk medicine for the treatment of diabetes, which has motivated several botanical, chemical and pharmacological studies. The objective of this research was to develop a protocol for callus induction in leaf explants of C. verticillata, aiming to provide support for further establishment of cell suspension systems for in vitro production of secondary metabolites. The leaves were cut into 1 cm2 explants, individually inoculated in test tubes on Murashige & Skoog culture medium supplemented with 3.0% sucrose, 0.6% agar, 2,4-D (0, 1, 2, and 4 mg L-1) and BA (0, 1, 2, and 4 mg L-1) in factorial combinations. On the 42nd day after inoculation, callus induction, percentage of the leaf area covered by callus cells (%LACC), and fresh weight of the explants were evaluated. No callus induction was observed without growth regulators. All the other treatments resulted in 100% induction. However, 2,4-D caused tissue necrosis in all the explants. In the media supplemented with BA and in the absence of 2,4-D, explants did not necrose and callus growth occurred. Highest percentages of LACC were observed in the media supplemented with 1.0 and 4.0 mg L-1 BA, in which all the explants presented 100% of the explant area covered by callus cells. The greatest fresh mass, 18.19 g, was achieved with 4.0 mg L-1 BA in the culture medium.